HUBUNGAN PENGETAHUAN, SIKAP DAN PRAKTIK TENTANG STANDARD OPERATIONAL PROCEDURE DENGAN KEJADIAN KECELAKAAN KERJA PADA BAGIAN TWISTING DI PT X CIREBON TAHUN 2017 - Idham Latif; Bayu Sela Priyatna; Terie Adi Pertiwi (JURNAL KESEHATAN INDRA HUSADA, 2017)
Every year, thousands of work accidents were occurred in workplace which causes victims, materials damage, and production disturbances. According to International Labor Organization (ILO) estimated that around 2.3 million people around the world have died caused of work accident and illness in every year, the work accident in industrial field also experienced by PT X Cirebon. On 2016, there were 30 cases of work accident occur outside or inside of PT X Cirebon. According to some researches, work accident is related to knowledge, attitude and practice of SOP. It needs to do research to reduce the work accident in PT X Cirebon. The relation between free variables (knowledge, attitude and practice workers of SOP) and bound variables (work accident) were tested with Chi-Square test.The result of research shows there is no relation between knowledge and worker’s attitude of SOP with work accident, but there is relation between practice workers of SOP and work accident. It has the same result of Kartika’s research (2017) that there is relation between compliance of job instruction and behavior safe workers. It can conclude that the practice workers of SOP are the causes of work accident in PT X Cirebon. There is suggestion to company, to give punishment to worker who disobeyed regulations related to K3.